Експресія антиапоптозних білків у тканинах колоректальної аденокарциноми при різних клінічних стадіях - Хижняк, С.В.; Сорокіна, Л.В.; Осинський, Д.С.; Дьомін, Є.М.; Войціцький, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The disbalance between the processes of cell division and cell death is the most inherent attribute of tumor cells. The aim of this work was to evaluate the expression levels of 3′-phosphoinositide-dependent protein kinase-1 (PDK 1) and antimitoptotic proteins Bcl-2 and Bcl-xL in the tumor tissues of surgically removed colorectal adenocarcinoma of different clinical stages. The estimated increased quantities of these signal proteins at the II-nd and IV-th carcinoma stages testify to the involvement of the precisely coordinated signal proteins to the processes of general programmed cell death inhibiting during the carcinogenesis.